Influence of fertilization, season, and forage species in presence of arbuscular mycorrhizae in a degraded andisoil of colombia (2011)
In the Colombian coffee zone much of the land has infertile soils with an ongoing accelerated degradation. As vegetation has changed from forest to transitory base (cassava cropping) and overgrazed pastures, ground cover has decreased resulting in increasing runoff. These changes have contributed to severe erosion, decline in soil fertility, productivity, soil structure, and water quality as well as loss of biodiversity. A field study was conducted at the farm “La Esperanza” (Mondomo, Department of Cauca, Colombia, South-America). The main objective was to determine the influence of fertilization, season and forage species in Arbuscular Mycorrhyzae in a degraded Andisol. One C4 forage grass (Brachiaria dictyoneura) and two C3 forage legumes (Arachis pintoi and Centrosema macrocarpum) and native vegetation grown under two fertilization levels, cultivated either in monoculture or in association and harvested at four different ages were evaluated. The numbers of mycorrizal spores in the soil and percentage of root infection of arbuscular mycorrhiza increased with age and varied with the species and season. We founded differences among forage grass and legume species under field conditions to form symbiosis with mycorrhizal fungi. Knowledge on these interspecific differences could contribute to developing better adapted forage systems to contribute recuperating the degraded soils of the Andean hillsides of Latin America.